Discursos docentes reveladores de concepções normatizadoras do corpo criança - Machado, Adrielli Silva Bielssa (Universidade Federal de São Carlos, 2026)
This undergraduate thesis aims to investigate the impacts that teaching discourses permeated by disciplinary and normative conceptions have on the child's body. It sought to answer the following research question: "How do teaching discourses, permeated by disciplinary and normative conceptions and by power relations, impact the child's body in the school context?". To this end, based on Foucault's theoretical framework, Garanhani's concept of the child's body, and Lira's concept of the child's body versus the student's body, through qualitative, bibliographical and narrative research on lived experiences, the study sought to reflect on the transition of violence and oppression of bodies (which were previously aimed at the physical body and have become subtle, constraining and offending without leaving visible marks) aimed at the "formation" of children who meet adult expectations, and to understand that this process is not neutral. Given that different issues emerged from the pedagogical scenes, this work discusses the silencing of children's voices and bodies; the importance of their participation and movement in learning processes; ableism, authoritarianism, and exclusion in relationships with children; discourses of crisis, disbelief, and hopelessness in childhood; the need to transform the conception of utility and productivity; and the importance of hope. Finally, the results indicate that aggressive, normative, and oppressive teaching discourses produce effects such as: silencing children; docility and control; reinforcement of hierarchies and inequalities; naturalization of symbolic violence; production of feelings of inadequacy, shame, or inferiority; and limitation of children's possibilities for expression, creation, and participation—phenomena that compromise their well-being and the construction of a democratic, inclusive education sensitive to the multiple ways of being and existing in childhood. Even with the numerous transformations already implemented in education, struggles and resistance are still necessary for the school to cease being a home of "adult-centric clichés" and become a place of acceptance, critical and loving learning, enabling social transformation.
Teacher discourses revealing normative conceptions of the child's body
Keywords: Corpo criança; Child's body; Docência; Teaching; Formação de professores; Teacher´s education; Ensino Fundamental; Elementary education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade